Proximal Interphalangeal Joint Arthroplasty Using the Wide-Awake Local Anesthesia No Tourniquet Technique. (June 2023) - Sharma, Sidharth; Ong, Jason; Putti, Amit
Background: Proximal interphalangeal joint (PIPJ) osteoarthritis is a common condition that results in pain, stiffness, and loss of function in the affected hand. Proximal interphalangeal joint arthroplasty is an effective treatment option when conservative methods have failed. The wide-awake local anesthesia no tourniquet (WALANT) technique to perform surgery carries advantages such as lack of tourniquet discomfort, reduces the staffing and costs associated with anesthesia and sedation, and allows faster recovery. We aimed to determine whether the WALANT technique was safe and effective in the context of PIPJ arthroplasty. Methods: Patients were enrolled retrospectively from January 2015 to October 2020 by examining operating theater records and surgeon logbooks. Electronic patient records were examined to obtain patient data. Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaires and Visual Analog Scale (VAS) for pain were sent by post to patients—with a separate DASH and VAS for each digit operated on. Results: Twenty-nine PIPJ arthroplasties were carried out using WALANT technique by 3 different surgeons all using the dorsal approach. All cases were successfully carried out as day-case procedures. There was a significant correlation with increasing VAS and increasing DASH score. Proximal interphalangeal joint arthroplasty improved range of motion from 28.9 ± 5.5° to 79.4 ± 13.3° ( P < .0001). Two cases developed complications related to surgery. Conclusions: Our study is the first to report the use of WALANT to perform PIPJ arthroplasty, and shows comparable results with traditional methods. Larger, multicenter prospective trials are required to determine the efficacy of this technique and to quantify its economical benefit.